PENDAMPINGAN PRAKTEK SHOLAT MENGGUNAKAN MEDIA KITAB FASHOLATAN DI PONPES AN NUR PUNGGING MOJOKERTO - Fitriyah, Khoirunnisail (STAI Hidayatut Thullab Kediri, 2023)
The aim of this community service activity is to improve the prayer skills of new students so that they are in accordance with Islamic law. This learning is guided by the Fasholatan book which is practical and easy to understand. The methods used in this community service activity are observation, direct interviews, mentoring, evaluation of results. Evaluation of the success of this service program is carried out by distributing questionnaires after the activity is carried out. The result of this service activity was a positive response given by the students to the prayer practice assistance activity using the fasholatan book at the An Nur Pungging Islamic boarding school, Mojokerto.